Practice pattern and use of serum peptide formulation in patients with alopecia: results of an opinion survey among dermatologists in India - Lanjekar, Rekha (International Journal of Research in Dermatology, 2020)
To evaluate practice pattern and preference for use of serum peptide formulation by dermatologists for the treatment of alopecia. Dermatologists in India were administered a questionnaire consisting of questions related to number of patients with alopecia seen every week, investigations, prevalence of nutritional deficiencies and use of serum peptide formulation in telogen effluvium (TE) and androgenetic alopecia (AGA). The responses were analysed as number and percentages. Out of 124 dermatologists, 38 (31%) reported that they see 11-15 patients with TE every week and 31 (25%) reported seeing 11-15 patients of AGA per week. According to 51 (41%) dermatologists, 40-60% patients with hair loss have some nutritional deficiency and 95 (77%) reported that iron deficiency profile, thyroid stimulating hormone (TSH), vitamin B1 and vitamin D level estimation is necessary in patients with TE. A total of 86 (69%) dermatologists preferred serum peptide formulation in patients with TE and AGA. Ninety nine (80%) and 75 (60%) dermatologists reported “very good” or “good” efficacy of serum peptide in TE and AGA respectively. Ninety nine (80%) dermatologists said, gender is not an important criterion for choosing a serum peptide in hair fall. For aesthetics related parameters, Folliserum (Abbott Health care Pvt Ltd) was rated as “Very good” and “Good” by 66 (53%) and 38 (31%) dermatologists respectively. According to dermatologists in India, nutritional deficiency is common in patients with alopecia. Majority of the survey participants rated Folliserum as “Very good” or “Good” for its efficacy and aesthetic parameters.